What constitutes quality in the Swiss initial vocational education and training dual system : an apprentice perspective - Sauli, Florinda [Verfasser]; Wenger, Matilde [Verfasser]; Berger, Jean-Louis [Verfasser] (My University, 2021)
"In Switzerland, the promotion of quality of initial vocational education and training (IVET) is stated in law. However, little is known about what characterizes this quality, especially from the perspective of the main actors of IVET. This study investigated the perceptions ofIVET quality from 320 apprentices enrolled in a dual IVET program. Two occupational fields were considered: technical and retail. A thematic analysis was performed on data collected through open-ended questions. Results revealed that the quality of IVET was multilayered and complex. Apprentices’ perceptions of high and low quality were grouped into three different levels of a more comprehensive system. The levels included elements referring to (1) the learning objects, (2) the social learning environment, and (3) the IVET context. Differences in the perceptions of quality between learning sites and occupational fields were also highlighted." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; L 6 Qualität; I 2.2.1 Westeuropa; 370; Berufsausbildung; Duales System; Ausbildungsqualität; Auszubildender; Ausbildungsbetrieb; Berufsschule; Berufsbereiche; Schweiz